2005
DOI: 10.1152/ajpendo.00310.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differing physiological effects of epinephrine in type 1 diabetes and nondiabetic humans

Abstract: Acute increases of the key counterregulatory hormone epinephrine can be modified by a number of physiological and pathological conditions in type 1 diabetic patients (T1DM). However, it is undecided whether the physiological effects of epinephrine are also reduced in T1DM. Therefore, the aim of this study was to determine whether target organ (liver, muscle, adipose tissue, pancreas, cardiovascular) responses to epinephrine differ between healthy subjects and T1DM patients. Thirty-four age- and weight-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Our data demonstrated that patients with T1DM have decreased neuroendocrine (glucagon and norepinephrine), metabolic [endogenous glucose production (EGP), glucose uptake (R d ), and glucose oxidation], cardiovascular (mean arterial pressure), and symptomatic responses but increased lipolytic responses to moderately elevated physiological levels of epinephrine compared with nondiabetic subjects (2).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Our data demonstrated that patients with T1DM have decreased neuroendocrine (glucagon and norepinephrine), metabolic [endogenous glucose production (EGP), glucose uptake (R d ), and glucose oxidation], cardiovascular (mean arterial pressure), and symptomatic responses but increased lipolytic responses to moderately elevated physiological levels of epinephrine compared with nondiabetic subjects (2).…”
mentioning
confidence: 71%
“…Previously, we (2) have investigated the integrated physiological effects of epinephrine independently of the confounding variable of hyperglycemia in a group of T1DM with average control and healthy nondiabetic subjects. Our data demonstrated that patients with T1DM have decreased neuroendocrine (glucagon and norepinephrine), metabolic [endogenous glucose production (EGP), glucose uptake (R d ), and glucose oxidation], cardiovascular (mean arterial pressure), and symptomatic responses but increased lipolytic responses to moderately elevated physiological levels of epinephrine compared with nondiabetic subjects (2).…”
mentioning
confidence: 99%
“…Although evidence of hepatic resistance to the effects of counterregulatory hormones is not strong, a recent report suggests attenuation of the effects of infused epinephrine on EGP in poorly controlled type 1 diabetes (32). In contrast to these findings, Berk et al (33) demonstrated enhanced glycemic responsiveness to epinephrine in type 1 diabetic subjects compared with nondiabetic subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Rates of glucose uptake were unchanged during the series of hypoglycemic clamps. Previous studies have demonstrated that the doseresponse effects of epinephrine to inhibit glucose uptake are relatively flat (33,34) in association with increasing the concentrations of the catecholamines from 600 to 1,000 pg/ml, producing limited actions. Similar to the findings in healthy humans, fluoxetine resulted in an increased response of cortisol during hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%